2010
DOI: 10.1093/brain/awq259
|View full text |Cite
|
Sign up to set email alerts
|

GPR56-related bilateral frontoparietal polymicrogyria: further evidence for an overlap with the cobblestone complex

Abstract: GPR56 mutations cause an autosomal recessive polymicrogyria syndrome that has distinctive radiological features combining bilateral frontoparietal polymicrogyria, white matter abnormalities and cerebellar hypoplasia. Recent investigations of a GPR56 knockout mouse model suggest that bilateral bifrontoparietal polymicrogyria shares some features of the cobblestone brain malformation and demonstrate that loss of GPR56 leads to a dysregulation of the maintenance of the pial basement membrane integrity in the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(168 citation statements)
references
References 36 publications
10
156
0
2
Order By: Relevance
“…PMG can affect part of the brain or the whole brain, and there can be overlapping features with COB-LIS as mentioned above [227]. PMG exist also as an isolated malformation or it may be associated with other brain malformations, such as corpus callosum agenesis and hypogenesis, cerebellar hypoplasia, PVH and SBH in patients that may present microcephaly, normocephaly or macrocephaly [237].…”
Section: 25a Polymicrogyria (Pmg)mentioning
confidence: 97%
See 1 more Smart Citation
“…PMG can affect part of the brain or the whole brain, and there can be overlapping features with COB-LIS as mentioned above [227]. PMG exist also as an isolated malformation or it may be associated with other brain malformations, such as corpus callosum agenesis and hypogenesis, cerebellar hypoplasia, PVH and SBH in patients that may present microcephaly, normocephaly or macrocephaly [237].…”
Section: 25a Polymicrogyria (Pmg)mentioning
confidence: 97%
“…In addition, GPR56 (G protein-coupled receptor) mutations have been reported in 14 patients with bilateral frontoparietal PMG (see below), and the phenotypes associated with these mutations were proposed as COB-like cortical dysgeneses due to the pathophysiological similarities with COB-LIS [227]. Indeed, homozygous or biallelic mutations in the GPR56 ligand, COL3A1 were also recently found associated with a COB-like malformation [228].…”
Section: A Type II Lissencephaly (Cobblestone)mentioning
confidence: 99%
“…Magnetic resonance images of BFPP brains reveal bilateral polymicrogyria with an anterior-to-posterior gradient, decreased white matter volume with associated bilateral signal changes, as well as brainstem and cerebellar hypoplasia. Histologic studies in a Adgrg1 (Gpr56) knockout mouse model and a human postmortem BFPP forebrain demonstrate that BFPP is a cobblestone-like cortical malformation, characterized by neuronal overmigration through a breached pial basement membrane (Li et al, 2008;Bahi-Buisson et al, 2010). Studies in Adgrg1 (Gpr56) knockout mice further demonstrated that ADGRG1 (GPR56) is essential for proper morphogenesis of the rostral cerebellum by its regulation of the external granule cell adhesion to the extracellular matrix proteins (Koirala et al, 2009).…”
Section: Skeletal Muscle and Bonementioning
confidence: 98%
“…Magnetic resonance imaging of BFPP brains shows numerous (poly) small (micro) gyri, which extend diffusely across the frontal and parietal lobes with a decreasing anterior-to-posterior gradient of severity (17)(18)(19)(20). Further studies in Gpr56 knockout mice and postmortem human BFPP brain specimen revealed that the histopathology of BFPP is a cobblestone-like cortical malformation (21,22). However, the molecular and cellular mechanisms of how GPR56 regulates brain development remain largely unknown.…”
mentioning
confidence: 99%